Mecanismos de ação do resveratrol na diferenciação neural in vitro e na sinalização purinérgica em camundongos infectados com Toxoplasma gondii - Bottari, Nathieli Bianchin (2018)
Central nervous system (CNS) development involves events that include the proliferation of neural precursor cells (NPCs) that differentiate and migrate in a process for creating connections and networks. In this context Toxoplasma gondii is an intracellular neuropathic parasite capable of influencing neural fate. T. gondii can cause neurotoxoplasmosis in humans, induces abortus, behavioral alterations and oxidative damage in host cells. However, the mechanism underlying neuropathogenesis in cerebral toxoplasmosis remains elusive. The purinergic system has recently emerged with significant signalling in the immune response against infections, including toxoplasmosis. The binding of extracellular nucleotides and nucleosides, especially adenosine trifosfate (ATP) and adenosine (ADO) to their P2X7, P2Y1, A1 and A2A receptors stimulate the activation of microglial cells as well as a pro and anti-inflammatory cytokines secretion contributing to the immune response against the parasite. Toxoplasmosis is a worldwide disease, with great zoonotic potential and difficult treatment; thus these hypotheses motivated the aim of this study. In the present study, we investigated the effects of resveratrol (RSV), a potent natural anti-inflammatory and antioxidant molecule found in grapes, in brain neurotransmission, as well as in proliferation/migration and neurogenesis of NPCs in embryos infected with T. gondii. For gain insights in the role of T. gondii during development of the neural steam cells, the NPCs were obtained from infected embryos using VEG strain of T. gondii. Thus, as NPCs proliferate in the presence of growth factors becoming multipotent and forming neurospheres. The results demonstrate that T. gondii increases the proliferation and migration of NPCs besides stimulating the glyogenesis to the detriment of neurogenesis. Among the concentrations tested, 1 and 10μm RSV exerted the struggles on the critical effect of NPCs. In addition, T. gondii infection modulated the activity of NTPDase and ADA enzymes in infected NPCs; an overexpression of P2X7 receptor and down expression of the A2A receptor were observed in infected NPCs. This modulation on the activity of enzymes stimulates the production of proinflammatory cytokines by host cells contributing to the inflammatory process. However, the treatment with RSV was able to reduce the activity of the NTPDase and ADA enzymes by inhibiting the P2X7 receptor and stimulated the transport of ADO to the intracellular medium via the A2A receptor, reducing cellular viability. Adult mice infected with T. gondii increased NTPDase and 5'-NT activities, but a reduction in ADA enzyme was observed. The results obtained are a greater hydrolysis of ATP, which binds to P2X7 and P2Y1 receptors. RSV exerted its neuromodulatory effect regulating ectonucleotidase enzymes and purinergic density receptors. Furthermore, RSV modulates extracellular adenosine binds to the A1 and A2A receptors and decrease oxidative damage. Fetal maternal transmission of T. gondii induces a depressive-like behavior and memory loss. Again, RSV exerts neuroprotection by repairing behavioral changes. Together, the results of this study propose the activation of purinergic signalling by T.gondii and demonstrate the neuroprotective effect mediated by RSV, suggesting this molecule as therapeutic potential for the treatment of neurotoxoplasmosis.